2002
DOI: 10.1021/ja0207798
|View full text |Cite
|
Sign up to set email alerts
|

NMR Determination of the Conformation of a Trimethylene Interstrand Cross-Link in an Oligodeoxynucleotide Duplex Containing a 5‘-d(GpC) Motif

Abstract: Malondialdehyde interstrand cross-links in DNA show strong preference for 5'-d(CpG) sequences. The cross-links are unstable and a trimethylene cross-link has been used as a surrogate for structural studies. A previous structural study of the 5'-d(CpG) cross-link in the sequence 5'-d(AGGCGCCT), where G is the modified nucleotide, by NMR spectroscopy and molecular dynamics using a simulated annealing protocol showed the guanine residues and the tether lay approximately in a plane such that the trimethylene tethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 42 publications
5
60
1
Order By: Relevance
“…The are not many studies (10,(12)(13)(14) on the toxicology of MDA. Draper et al showed that its administration in a range of 0.1-10 µg/g/day to mice produces dose-dependent neoplastic changes in the liver (14).…”
Section: Resultsmentioning
confidence: 99%
“…The are not many studies (10,(12)(13)(14) on the toxicology of MDA. Draper et al showed that its administration in a range of 0.1-10 µg/g/day to mice produces dose-dependent neoplastic changes in the liver (14).…”
Section: Resultsmentioning
confidence: 99%
“…(33). The changes in the aromatic region chemical shifts upon Fe 2+ binding in this study were approximately 0.1–0.25 p.p.m.…”
Section: Discussionmentioning
confidence: 99%
“…62 When the N 2 -dG:N 2 -dG trimethylene linkage (37), a surrogate for the non-observed cross-link in the 5′-GpC-3′ sequence, was constructed in d(TCCXCGGA) 2 , its structure was distorted, and its T m was reduced. 59,63 Interstrand Cross-linking of (6R) and (6S) Crotonaldehyde 1,N 2 -PdG AdductsRing-opening of the diastereomeric 1,N 2 -dG adducts 11 and 12 was incomplete at pH 7 when placed opposite dG in duplex DNA. The incomplete ring-opening was attributed to the positioning of the CH 3 groups to avoid steric clash with N3 of guanine, which becomes significant in the N 2 -(1-methyl-3-oxopropyl)-dG aldehydes (3,4).…”
mentioning
confidence: 99%